ANALISIS WEEKEND EFFECT TERHADAP RETURN SAHAM DI BURSA EFEK INDONESIA - Luhgiatno . (STIE Pelita Nusantara Semarang, 2012)
This research investigate the Weekend Effect Phenomena that explain stock price inclined rise on Friday and declined on Monday. Then, this research investigate the analysis of Weekend Effect toward stock return in Indonesia Stock Exchange that purpose to analyze the difference of stock return on Friday and Monday.The population is Stock registered in Indonesia Stock Exchange, and sample is: IHSG and LQ45 Index in Jan 2010 to Des 2011. Dependen Variable is Stock Return and Independen Variable is Weekend Effect which trade on Friday and Monday. Data used in this study is secondary data from ISX, that is IHSG and LQ45 Index.This study show that there is no difference on Stock Return on Friday and Monday on IHSG and LQ45 Index. This prove by significancy value of IHSG 0,658 > 0,05 and LQ45 Index 0,560 > 0,05.